Topological Methods in Data Analysis and Visualization V: Theory, Algorithms, and Applications - Carr, Hamish; Fujishiro, Issei; Sadlo, Filip; Takahashi, Shigeo (Mathematics and Visualization, 2020)
Persistence -- Scalar Topology -- Time-Varying Topology -- Multivariate Topology -- Other Forms of Topology.